Genetic and physical interactions between Polη and Rev1 in response to UV-induced DNA damage in mammalian cells - Tonghui Bi (Nature Portfolio, 2021)
Abstract In response to UV irradiation, translesion DNA synthesis (TLS) utilizes specialized DNA polymerases to bypass replication-blocking lesions. In a well-established polymerase switch model, Polη is thought to be a preferred TLS polymerase to insert correct nucleotides across from the thymine dimer, and Rev1 plays a scaffold role through physical interaction with Polη and the Rev7 subunit of Polζ for continual DNA synthesis. Defective Polη causes a variant form of xeroderma pigmentosum (XPV), a disease with predisposition to sunlight-induced skin cancer. Previous studies revealed that expression of Rev1 alone is sufficient to confer enhanced UV damage tolerance in mammalian cells, which depends on its physical interaction with Polζ but is independent of Polη, a conclusion that appears to contradict current literature on the critical roles of Polη in TLS. To test a hypothesis that the Rev1 catalytic activity is required to backup Polη in TLS, we found that the Rev1 polymerase-dead mutation is synergistic with either Polη mutation or the Polη-interaction mutation in response to UV-induced DNA damage. On the other hand, functional complementation of polH cells by Polη relies on its physical interaction with Rev1. Hence, our studies reveal critical interactions between Rev1 and Polη in response to UV damage.